2022
DOI: 10.1186/s13568-022-01497-5
|View full text |Cite
|
Sign up to set email alerts
|

A biostatistical approach for augmenting rare bianthraquinone antibiotic production by Streptomyces sp. RA-WS2 using Taguchi design

Abstract: Consistent production of bioactives from microbial sources remains a big challenge for fermentation based bio-processes. Setomimycin, a rare 9,9'-bianthrylanthracene antibiotic reported to be active against Gram positive bacteria i.e. Staphyloccocus aureus, Bacillus subtilis, Bacillus cereus, and Mycobacterium smegmatis, including mycobacteria is one of the least exploited antibiotic. Present work aims to enhance and maximize setomimycin production using One Factor at a Time (OFAT) approach, followed by Taguch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…In this study, the ANN-GA model demonstrated a superior performance over the RSM model in optimizing the production of 4 ′ -N-demethyl-vicenistatin by S. parvus SCSIO Mla-L010/∆vicG, both in terms of example verification and overall model performance. It has been widely acknowledged that researchers in the field of microbial fermentation optimization commonly employ conventional statistical methods, including the OFAT approach [74], orthogonal experiments [75], PBD [76][77][78], and RSM [14,79,80], for optimization purposes. For instance, the RSM, whether it is the Box-Behnken design (BBD) or CCD, is generally applicable when there are no more than four experimental factors.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the ANN-GA model demonstrated a superior performance over the RSM model in optimizing the production of 4 ′ -N-demethyl-vicenistatin by S. parvus SCSIO Mla-L010/∆vicG, both in terms of example verification and overall model performance. It has been widely acknowledged that researchers in the field of microbial fermentation optimization commonly employ conventional statistical methods, including the OFAT approach [74], orthogonal experiments [75], PBD [76][77][78], and RSM [14,79,80], for optimization purposes. For instance, the RSM, whether it is the Box-Behnken design (BBD) or CCD, is generally applicable when there are no more than four experimental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Each of the concentrations represented 1 level ( Table 1 ). Thus, a 3-factor, 3-level L9(3 3 ) OED was selected and applied to the experiments ( Table 2 ) ( Manhas, Kumar & Chaubey, 2022 ).…”
Section: Methodsmentioning
confidence: 99%